Predicting chemotherapeutic response and toxicity in colorectal cancer. (August 2013) - Diakos, Connie I; Chua, Wei; Charles, Kellie A; Howell, Viive M; Clarke, Stephen J
SUMMARY While treatment for colorectal cancer has evolved significantly over the past 10 years with the introduction of active chemotherapeutic agents and targeted therapies, this has been at the cost of increased toxicity for patients; and significant financial burden for governments and patients. Predicting clinical outcomes, especially given the largely elderly patient population involved, is therefore paramount. This review seeks to summarize existing data regarding the prediction of response and toxicity to chemotherapy agents currently used in the treatment of colorectal cancer.